Perancangan Sistem Lost & Found di Universitas Nasional Karangturi Berbasis Web - Aurelio Akeno Adiwijaya; Ahmad Nugroho (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Reported of lost and found items at Unkartur was still done conventionally. Campus residents usually reported to security regarding the loss they experienced. However, the process of reporting and searching for lost items required a lot of time, energy, and money. Therefore, this study aimed to design a system for reporting lost and found items, especially in the Unkartur campus environment. The methods used in this study were Unified Modeling Language (UML) and Entity Relationship Diagram (ERD). This system was useful in managing lost and found item data to be more structured and efficient. The results of the design of this Lost & Found system could be a solution in the process of searching for lost items and returning found items in the Unkartur campus environment.